Epidemiology, Antibiotic Susceptibility and Serotype Distribution of Streptococcus pneumoniae Associated with Invasive Pneumococcal Disease in British Columbia - A Call to Strengthen Public Health Pneumococcal Immunization Programs - Mark Bigham; David M Patrick; Elizabeth Bryce; Sylvie Champagne; Carol Shaw; Wrency Wu; Helen Ng; Diane Roscoe; Jacques Roy; Judy Isaac-Renton (Canadian Journal of Infectious Diseases)
BACKGROUND: This study examined the epidemiology, antibiotic susceptibility and serotype distribution of Streptococcuspneumoniae associated with invasive pneumococcal disease (IPD) in British Columbia.